Rice husk to charcoal converter machine (vertical type) / Mohd Khairul Anuar Shah Hassan - Shah Hassan, Mohd Khairul Anuar (2010)
Rice husk charcoal converter machine is very important to our country because almost all citizens in Malaysia eat rice, then we need one machine to help the paddy industry grow easily and faster with high quality. This project is to design and fabricate a machine to convert the rice husk into char stage for the nursery growing process The first phase of the project is to identify the strategy in producing char so as to fulfill the requirements of paddy plantation. The solution here is to design and fabricate a prototype of converting rice husk based on problems and user requirements in the agriculture sector. From the information gathered and studied, problems had been identified and the user requirement had been listed. The user requirement will then be analyzed in order to get the important features and produce engineering specification of converting the rice husk. The analysis of the requirement and the design specification has been used to create the system and the design concept of the converting rice husk. Finally, the furnace of the rice husk converter machine has been fabricated successfully.